PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Nadillah, Rani Fitrah; Munastiwi, Erni; Nurdiana, Elqy (STKIP Pesisir Selatan, 2026)
Objective: Leadership by principals plays a critical role in enhancing teacher professionalism across different education levels, including early childhood education. The shifting needs of 21st-century education necessitate that principals function not just as administrative managers but also as learning leaders who can continuously foster, motivate, and enhance teacher competencies. This research seeks to systematically analyze how principal leadership influences the enhancement of teacher professionalism based on recent studies. Methods: A Systematic Literature Review (SLR) with a descriptive qualitative approach was employed, analyzing 20 national and international scientific articles published between 2019–2025 from reputable journal databases, through identification, selection using inclusion and exclusion criteria, data extraction, and thematic synthesis. Results: The findings show that transformational leadership and instructional leadership are the most consistently effective strategies in enhancing teacher professionalism, encompassing pedagogical, professional, social, and personal competencies. Novelty: This study provides a synthesized evidence base from recent literature (2019–2025) confirming that adaptive and collaborative principal leadership approaches are pivotal in supporting educational quality improvement, particularly in the early childhood education context.